Rectus sheath hematoma: a potentially life threatening complication following caesarean delivery - Dube, Sonal; Dube, Meenakshi; Dube, Saumitra (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Rectus sheath hematoma (RSH) is a rare but potentially life threatening complication of caesarean delivery. The nonspecific nature of entity, lower incidence of disorder and acute presentation may posses’ difficulty in timely recognizing this. Present patient presented as acute abdominal pain 38 hours post caesarean section. This is an attempt to increase the awareness of this rare but potentially grave condition, as timely diagnosis and fast intervention saved present patient.